Hubungan antara Iklim Kelas dengan Motivasi Belajar pada Mahasiswa - Ayu Novita Dwi Aryani; Asmadi Alsa (Gadjah Mada Journal of Psychology (GamaJoP), 2016)
The purpose of this study was to examined the correlation between classroom climate and learning motivation. Dependent variable was learning motivation which measured used Learning Motivation Scale by McCown, Driscoll and Roop (1996). Independent variable was classroom climate which measured used What Happening In This Class (WIHIC) questionnaire by Fraser, Fisher and Mc Robbie (1996). Hypothesis of this study was “there was positive correlation between classroom climate with learning motivation”. Subject in this study were 143 college students who studied in Faculty of Psychology, X University. Data analyze method that used was product moment correlation technique from Pearson. Data analyze showed that there was very significant positive correlation between classroom climate and learning motivation, with r = 0,450 and p = 0,000 (p<0,01), so the hypothesis can be accepted.